THE ROLE OF GREEN HUMAN RESOURCE PRACTICES IN PROMOTING GREEN SERVICE BEHAVIOUR - Che Mohd Syaharuddin Che Cob; Siti Nur Zahirah Omar; Mohd Hafeez Al-Amin Abdul Wahab; Hassanul Firman Md Apandi; Azahar Hj Yusoff (International Journal of Accounting, Finance and Business, 2024)
This study explores the role of green human resource (HR) practices in promoting green service behavior within organizations. As sustainability becomes a critical concern, organizations are increasingly recognizing the need to align their HR practices with environmental goals. Green HR practices encompass strategies and initiatives aimed at fostering environmentally friendly behaviors among employees, ultimately leading to the delivery of green services. They are grounded by the Resource-Based View (RBV) theory. Furthermore, this study discusses the significance of integrating green HR practices with other organizational systems and processes, such as green operations and green marketing, to create a coherent and consistent approach to sustainability. This alignment ensures that green service behavior is not just an isolated practice but a holistic organizational effort. By understanding the role of green HR practices in promoting green service behavior, organizations can develop strategies to create a sustainable work environment, enhance employee commitment, and meet the growing demand for environmentally conscious services. This study also provides a concise overview of the topic, setting the stage for further exploration of the underpinning theories and findings related to the role of green HR practices in promoting green service behavior. This paper makes a valuable contribution to the existing body of knowledge by enhancing conceptual understanding of human resource practices in promoting green service behavior.